Pengaruh Pola Asuh Orang Tua Strict Parents Terhadap Sikap Jujur Anak - Nurul Faizah; Rani Diah Febriyani; Aisyah Putri Maulida (CV. ULIL ALBAB CORP, 2026)
This study examines how strict parenting practices shape children’s honesty and psychosocial development. Using a descriptive qualitative field approach, data were collected through in-depth interviews with parents and children, direct observation of children’s behavior, and a review of relevant literature on parenting styles. The findings show that strict parenting is characterized by high control, rigid rules, and demanding expectations, often accompanied by limited emotional support. While such an approach is intended to cultivate discipline and responsibility, it may also generate adverse outcomes, including reduced self-confidence, emotional suppression, and tendencies toward dishonesty. Empirical evidence from two female respondents reveals contrasting experiences. The first reported a perceived lack of parental trust, leading to concealment of information and reluctance to communicate personal issues, despite recognizing parental care and protection. The second, an only child, experienced intensive supervision alongside academic support, which helped prevent engagement in negative behaviors but constrained emotional expression and autonomy. Overall, the study demonstrates that strict parenting produces ambivalent effects: it can reinforce behavioral control yet undermine emotional well-being and openness. The findings underscore the importance of balancing discipline with supportive communication and trust to foster honesty and healthy character development in children.